Report on proposed new interior design of Da Vinci Creative Art Centre for Da Vinci Creative Kids at Jalan Pekeliling Tasek, Taman Caning, 31400 Ipoh, Perak / Nurul Hazwani Izzati Rahmat - Rahmat, Nurul Hazwani Izzati (Faculty of Architecture, Planning and Surveying, 2011)
Final student in Diploma Architecture needs to come out with project report in order to understand the whole final project in every aspects started from basic level to final presantatation. The final project is proposed new design scheme of Creative Art Centre for Da Vinci Creative Kids at Jalan Pekeliling Tasek, 31400 Ipoh, Perak.Appropriate internal design will create a pleasant and conducive atmosphere for the children. The selection of this project is based on the issues highlighted by the Malaysian society is currently so much to influence the creative minds of children.Environments with plenty of space for art could have an impact on the development of children's creativity. In addition, in terms of the psychological aspects of the impact will affect the mind and the child's growth which in turn have a positive impact in terms of sociological aspects of personality and society. Internal decorations are also further promote the interaction of children to an atmosphere of a comfortable and conducive leaming. Modeling work to build confidence and satisfaction of children in the production of art. In conclusion this proposal is the new design scheme which make the design process need to be research in every aspect require.